Total Synthesis and Structural Elucidation of Cryptolatifolione - Novaes, Luiz F. T. (2015)
An enantioselective total synthesis of Cryptolatifolione and its C-8 epimer is presented in a protecting-group-free fashion. The synthesis relied on the use of a catalytic double Krische allylation, catalytic olefin metathesis and a C-H oxidation. Comparison of spectroscopical data of the synthetic isomers and natural product made possible the unequivocally elucidation of the absolute configuration of Cryptolatifolione.